Internet jako narzędzie komunikacji politycznej w społeczeństwie obywatelskim - Zawadzki, Janusz (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
We are currently witnessing an ongoing information revolution. It creates new standards of obtaining and managing information in various organizations, including political ones. G. Rydlewski justifiably claims that the information revolution is characterized by several features: the factor of territorial union decreases in importance, whereas the significance of channels of communication flow increases at the expense of classical instruments of political power. Power shifts from the management of resources to themanagement of flows. Some new technologiesmake some of themethods formerly applied by politicians useless. A so-called political cyberspace is emerging. The consequences of this process may involve extensive transformations in the way power is exercised. The scope of the issues involving themechanisms of direct democracy will expand.By this token the realmof the functioning of civic societywill also expand.